2007
DOI: 10.1007/s00383-007-2010-y
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic gastric volvulus in infants and children: who should be treated surgically?

Abstract: Gastric volvulus was first described by Berti in 1966. Whereas acute gastric volvulus is very rare, chronic gastric volvulus on the other hand is being diagnosed with increasing frequency. This is attributed to the liberal use of barium meal for the evaluation of infants and children with repeated attacks of vomiting and recurrent chest infection. This report describes our experience in the management of 36 infants and children with acute and chronic gastric volvulus. Their medical records were retrospectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 7 publications
1
20
0
Order By: Relevance
“…Gastric volvulus is an abnormal rotation of the stomach leading to partial or total obstruction, and according to the axis of rotation, it is classified into organoaxial, mesentericoaxial, and mixed [7–11]. In mesentericoaxial volvolus, the stomach rotates around an imaginary axis passing through the greater and lesser curvatures, while in organoaxial, the stomach rotates around an imaginary axis passing between the esophagogastric junction and the pylorus [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gastric volvulus is an abnormal rotation of the stomach leading to partial or total obstruction, and according to the axis of rotation, it is classified into organoaxial, mesentericoaxial, and mixed [7–11]. In mesentericoaxial volvolus, the stomach rotates around an imaginary axis passing through the greater and lesser curvatures, while in organoaxial, the stomach rotates around an imaginary axis passing between the esophagogastric junction and the pylorus [7].…”
Section: Discussionmentioning
confidence: 99%
“…In mesentericoaxial volvolus, the stomach rotates around an imaginary axis passing through the greater and lesser curvatures, while in organoaxial, the stomach rotates around an imaginary axis passing between the esophagogastric junction and the pylorus [7]. Organo-axial volvolus is the commonest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While other studies have also highlighted the importance of a background including failure to thrive and recurrent chest infection 6. Furthermore, there is emerging evidence to suggest that gastric volvulus is associated with GORD,5 , 6 and a mobile spleen,6 an association that should not be surprising given the role of these structures in maintaining the normal position of the stomach. Our case report supports this emerging consensus.…”
Section: Discussionmentioning
confidence: 99%
“…While strangulation necessitates immediate surgical referral, less severe cases provide a greater degree of debate; some argue that chronic gastric volvulus should always be managed surgically in order to prevent an, as yet, unproven potential progression to acute volvulus; however, there does not appear to be a basis for this in the literature. A recent publication has suggested that treatment should be based upon the severity of symptoms such that those with mild symptoms should be treated conservatively and those with severe symptoms should be treated surgically 6. At present an evidence-based classification of symptoms into severe and mild has not been elucidated, if indeed such a classification exists.…”
Section: Discussionmentioning
confidence: 99%